Cultivo de milheto fertirrigado com água cinza - Sotero, Allana Rayra Holanda (2019)
Reuse water is an alternative that allows the coexistence with the semi-arid, minimizing the effects of the long periods of drought and contributes for familiar agriculture. Being graywater an important source of water and nutrients, it is necessary to evaluate many cultures development when fertirrigated with raw or diluted graywater. Millet, for being a fairly rustic crop, adapts to the adverse environment conditions and presents good fodder productivity. The aim of this work was to analyze development, production, nutritional status and bromatological quality of millet fertirrigated with gray water and well water in different proportions ( T1 - 100% well water; T2 - 25% treated gray water plus 75% well water; T3 - 50% treated gray water plus 50% well water; T4 - 75% treated gray water plus 25% well water and T5 – 100% treated gray water). The experiment was carried out in vases filled with substrate in a greenhouse. The experimental design was randomized blocks with five treatments and six replicates (5 x 6), totaling 30 experimental plots. The results show that the use of treated gray water on fertirrigation was viable for millet’s production, having on the dilution of 50% of treated gray water plus 50% of well water better nutritional and bromatological quality. It was not found elements that could limit the use of gray water for fertirrigation